PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP TINDAKAN KRIMINALITAS DI PROVINSI-PROVINSI DI INDONESIA - Nurhaz Winda; Sri Ulfa Sentosa (Universitas Negeri Padang, 2021)
This study aims to determine the extent of the influence of economic growth on criminal acts in Indonesia, the effect of education level on criminal acts in Indonesia, the effect of unemployment rate on criminal acts in Indonesia, theeffect of poverty level on criminal acts in Indonesia, and the influence of economicgrowth, education level, the unemployment rate and the poverty rate togetheragainst criminal acts in Indonesia. This type of research is descriptive andassociative. The data used is secondary data. This study uses panel data, whichuses data from 32 provinces in Indonesia in the period from 2014 to 2019 using the Fixed Effect Model approach. The results of this study indicate that: (1) Economic growth has a positive and insignificant effect on criminal acts in Indonesia; (2) Education level has a negative and significant effect on criminal acts in Indonesia; (3) The unemployment rate has a positive and significant effect on criminal acts in Indonesia; (4) The poverty rate has a negative and insignificant effect on criminal acts in Indonesia.